Respuesta :
Answer:
Equation B, C and E have solution x = 3.
Step-by-step explanation:
We are given the following equations in the question:
1)
[tex]\displaystyle\frac{1}{2}x - 4 = 2\\\\\Rightarrow \frac{1}{2}x = 6\\\\\Rightarrow x = 12[/tex]
2)
[tex]0.4x - 0.8(x - 4) = 1.3x - 1.9\\\Rightarrow 0.4x-0.8x+3.2 = 1.3 x -1.9\\\Rightarrow -0.4x + 3.2 = 1.3x - 1.9\\\Rightarrow1.7x = 5.1\\\Rightarrow x = 3[/tex]
3)
[tex]\displaystyle\frac{1}{4}x + 7 = \frac{31}{4}\\\\\Rightarrow \frac{1}{4}x = \frac{31-28}{4} = \frac{3}{4}\\\\\Rightarrow x =3[/tex]
4)
[tex]x - 2(x + 4) = x + 2\\\Rightarrow x - 2x-8=x+2\\\Rightarrow -x-8=x+2\\\Rightarrow 2x = -10\\\Rightarrow x = -5[/tex]
5)
[tex]3(x + 4) - x = 18\\\Rightarrow 3x +12-x = 18\\\Rightarrow 3x-x = 6\\\\\Rightarrow x = \displaystyle\frac{6}{2} = 3[/tex]
Equation B, C and E have solution x = 3.